THE EFFECT OF PRENATAL MASSAGE ON LOW BACK PAIN INTENSITY IN THIRD TRIMESTER PREGNANT WOMEN AT INDRASARI REGIONAL HOSPITAL, RENGAT, IN 2026 - Amroati Soleha; Wira Ekdeni; Fajar Sari T; Rifa Yanti (Adisam Publisher, 2026)
One of the most common complaints experienced by pregnant women, especially during the third trimester, is low back pain. This pain occurs due to increased body weight, changes in body posture, and the influence of the relaxin hormone, which causes the ligaments around the pelvis and spine to soften. Prenatal massage is an intervention that can help reduce the level of back pain. Objective: To determine the effect of prenatal massage on the intensity of low back pain in third trimester pregnant women at Indrasari Regional Public Hospital Rengat. Method: This final project employed a quasi-experimental design with a one-group pretest–posttest approach. Results: The results of the bivariate analysis using the Paired Samples Test showed a p-value of 0.000 < 0.05 for the intensity of low back pain. Discussion: Prenatal massage can improve the physical comfort of pregnant women by providing a relaxation effect on muscles experiencing tension due to postural changes during pregnancy. Conclusion: There is an effect of prenatal massage on the intensity of low back pain in third trimester pregnant women at Indrasari Regional Public Hospital Rengat in 2026.